Research trends of cellular immunotherapy for primary liver cancer: A bibliometric analysis - Xiang'an Wu; Bao Jin; Xiao Liu; Yilei Mao; Xueshuai Wan; Shunda Du (Taylor & Francis Group, 2024)
Cellular immunotherapy has shown considerable potential for the treatment of primary liver cancer (PLC), particularly hepatocellular carcinoma (HCC), although it is in the early stages of development. This study used bibliometric methods to delineate the evolution of research on cellular immunotherapy for PLC. Data were sourced from the Web of Science Core Collection (WoSCC) on April 22, 2024. Using the "Bibliometrix" R package, we examined primary bibliometric features, collaboration frequency between countries, and article output of the journals. Furthermore, we employed VOSviewer for coauthorship analysis and visualization and CiteSpace to assess keyword co-occurrence, as well as to spotlight keywords and references with the strongest citation bursts. Our analysis encompassed 492 publications focused on PLC and cellular immunotherapy, and we pinpointed China, Japan, and the USA as the foremost contributing nations and identified "Cancer Immunology Immunotherapy" as the journal with the most contributions in this area. Sun Yat-sen University emerged as the institution with the most significant output, and Li Zonghai authored the greatest number of leading articles. Prominent keywords that displayed a notable citation burst in the later years included "chimeric antigen receptor," "combination therapy", "CAR-T cells," "TCR-T cells," and "liver transplantation." This bibliometric study outlined a foundational knowledge framework, surveyed over three decades of research on cellular immunotherapy for PLC, and revealed the key players and trends, thereby offering a thorough understanding of the field, especially in relation to HCC.